The management of sinogenic peri-orbital abscess - Raja Lope Ahmad, Raja Ahmad Al'konee; Abdullah, Fahmi; Abd. Aziz, Azian; Jwda, Adnan O. (Faculty of Medicine, International Islamic University Malaysia, 2004)
Complication following from infection of the paranasal sinus still occur, despite the broad use of antibiotic. Sinusitis is the commonest cause of orbital inflammation. The orbital complications are still threatening to the vision and occular movement and even to life. Sinogenic orbital inflammation occurs frequently in children. A case of orbital complications in acute sinustis is presented and the pathogenesis and management are discussed.